Mathematical model on the cellulase enzymes production as a function of viscosity / Fahimeh Abdeyazdan - Abdeyazdan, Fahimeh (2011)
As cellulosic material is the most abundant and renewable source of organic matter, ethanol can be produced cheaply from cellulosic waste. The cellulose must be hydrolyzed to glucose before it can be fermented to ethanol. The enzymatic hydrolysis of cellulose using cellulase enzymes is considered an environmental- friendly and less energy intensive alternative. White-rot fungi belong to the wood-destroying basidiomycetes and are well known as the only micro-organisms responsible for the enzyme hydrolysis of all major wood polymers, including lignin, cellulose and hemicelluloses. On the other hand, the production cost of cellulase enzymes is a limitation in ethanol fermentation. Therefore, the goal is to produce the enzymes economically by means of high-yield cellulase fermentation. Different type of bacteria and fungi can be used to achieve to this goal. In the present study, the ability of Pycnoporus sanguineus, a white rot fungus to produce cellulase was investigated since there are no reports of its cellulase production available. Different types of basal media were tested and enzyme activity was measured in the presence of cellulose powder, carboxymethylcellulose (CMC), Tween 80 and yeast extract. The cost of each medium is an important consideration. The highest amount of reducing sugar production was observed when CMC and Tween 80 were used as the components of the medium. This formulation is the most cost effective among the medium formulation. The study also presents the development of a mathematical model for cellulase production in submerged fermentation as a function of medium’s viscosity. To achieve this, the fungus was grown in two different media on agar plates. Then, the inoculation was carried out from these plates to a medium formulation in the shake flasks using variable concentration of CMC for determination of CMCase activity. Enzyme activity and viscosities of media were measured simultaneously. Mathematical function was explored for each media and then a unique model was reported for each media.